The Influence of Gold Price, World Oil Price, and Unemployment on Inflation - Arif Surahman; Nani Rusnaeni; Iman Lubis (Yayasan Pendidikan Penelitian dan Pengabdian Al-amsi, 2023)
This research examines the gold price, world oil price, and unemployment on inflation The data is from 2002 to 2022. The model are used ARIMA, ARCH, and GARCH. Type of data are time series. Gold price is stationary in data level. World oil price is stationary in first difference. Unemployment is stationary data in second difference. Gold price has not affected on difference inflation. Difference world oil price has not affected on difference inflation. Double difference unemployment has not affected on difference inflation. Gold price, difference oil price, and double difference unemployment have not affected on difference inflation simultaneously.